2021
DOI: 10.1108/cg-04-2020-0119
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and financial distress: Asian emerging market perspective

Abstract: Purpose The purpose of this paper is to examine the impact of corporate governance index (PAKCGI) on firm financial distress for a sample of 152 non-financial firms listed at Pakistan Stock Exchange (PSX) over the period from 2003 to 2017. Design/methodology/approach To examine the impact of PAKCGI on financial distress (Altman Z-Score), random effect model is applied. The PAKCGI is a self-constructed index based on the five important factors of corporate governance practices, i.e. board of directors, audit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
26

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(146 citation statements)
references
References 52 publications
(67 reference statements)
6
73
0
26
Order By: Relevance
“…The results of the fifth hypothesis test indicate that a larger board size can increase the likelihood of financial distress. This is similar to the findings of Helena and Saifi (2018), Salloum et al (2013), Siagian (2010), andYounas et al (2021). A larger board of directors usually causes an increase in two main problems, communication and coordination which The Effect of Board and Ownership Structure … Journal of Accounting and Investment, 2021 | 618 can slow down the decision-making process (Helena & Saifi, 2018;Salloum et al, 2013;Younas et al, 2021).…”
Section: Hypothesis Test Results and Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The results of the fifth hypothesis test indicate that a larger board size can increase the likelihood of financial distress. This is similar to the findings of Helena and Saifi (2018), Salloum et al (2013), Siagian (2010), andYounas et al (2021). A larger board of directors usually causes an increase in two main problems, communication and coordination which The Effect of Board and Ownership Structure … Journal of Accounting and Investment, 2021 | 618 can slow down the decision-making process (Helena & Saifi, 2018;Salloum et al, 2013;Younas et al, 2021).…”
Section: Hypothesis Test Results and Discussionsupporting
confidence: 82%
“…The Effect of Institutional Ownership on the Likelihood of Financial Distress Helena and Saifi (2018) and Younas et al (2021) found that companies with large institutional ownership can avoid financial distress. Li et al (2020) explains that the presence of institutional investors will reduce the possibility of financial distress to occur because institutional investors have the expertise and ability to detect companies that are eligible for investment, so companies with large institutional ownership will be trusted to have better performance.…”
Section: Resource Dependency Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Yu et al (2020) took an opposing stance, claiming a positive correlation to the block holder's ownership on disclosure. From the preceding, the block holder may carry a particular agenda that may conflict with the interests of the public of stakeholders (Younas et al, 2021). The block holder may monopolize the information to distinguish it from the rest of the stakeholders.…”
Section: Block-holder Ownershipmentioning
confidence: 99%